2020
DOI: 10.1093/ehjcvp/pvaa011
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality, stroke, and bleeding in patients with atrial fibrillation and valvular heart disease

Abstract: Aims  To compare the risk of all-cause mortality, stroke, and bleeding in patients with atrial fibrillation (AF) and valvular heart disease (VHD) treated with vitamin K antagonist (VKA) or factor Xa-inhibitors (FXa-I; rivaroxaban and apixaban). Methods and results  We cross-linked data from Danish nationwide registries identifying patients with AF and VHD (aortic stenosis/insufficiency, mitral insufficiency, bioprosthetic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Future studies examining the optimal antithrombotic management in each subgroup of EHRA Type 1 VHD and EHRA Type 2 VHD are needed. Several studies have examined the effectiveness and safety of NOAC vs warfarin in AF patients with VHD, primarily in patients with EHRA Type 2 VHD 25‐32 . Meta‐analyses of post hoc analyses of previous randomised trials examining NOAC vs warfarin in AF patients with VHD showed that when pooling the results there was a reduced risk of thromboembolism in the NOAC group and no difference in the risk of major bleeding 33‐36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies examining the optimal antithrombotic management in each subgroup of EHRA Type 1 VHD and EHRA Type 2 VHD are needed. Several studies have examined the effectiveness and safety of NOAC vs warfarin in AF patients with VHD, primarily in patients with EHRA Type 2 VHD 25‐32 . Meta‐analyses of post hoc analyses of previous randomised trials examining NOAC vs warfarin in AF patients with VHD showed that when pooling the results there was a reduced risk of thromboembolism in the NOAC group and no difference in the risk of major bleeding 33‐36 .…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses of post hoc analyses of previous randomised trials examining NOAC vs warfarin in AF patients with VHD showed that when pooling the results there was a reduced risk of thromboembolism in the NOAC group and no difference in the risk of major bleeding 33‐36 . However, in several comparative analyses based on real‐world data, the benefits of NOAC compared with warfarin were inconsistent 25‐28,32 . Until more evidence regarding the antithrombotic management of this population is available, clinicians are encouraged to use the EHRA classification and international guideline recommendations for guidance regarding stroke prevention in AF patients with VHD 11…”
Section: Discussionmentioning
confidence: 99%
“…Five real-world retrospective studies have also been conducted concerning the use of DOACs for VAF (Table 1). The retrospective cohort study using the Danish National Patient Registry by Strange et al 28 found no significant differences in stroke/SEE, major bleeding, and all-cause mortality rates between the DOAC (rivaroxaban or apixaban) and warfarin groups. However, this study relied on diagnostic codes for reporting outcomes.…”
Section: Resultsmentioning
confidence: 97%
“…[Insert figure 1] June 30, 2017. This study identified data from nationwide Danish registries with follow up until death, event, migration, switch, or discontinuation of treatment (11). The baseline characteristics of included studies were extracted and has been listed in table 1.…”
Section: Study Selectionmentioning
confidence: 99%